Структура поля приземного ветра над Мировым океаном - Еремеев, В.Н.; Букатов, А.Е.; Бабий, М.В.; Букатов, А.А. (Геоінформатика, 2014)
На основе среднемесячных значений компонент вектора скорости приземного ветра за период 1948–2012 гг. выполнено исследование внутригодовой изменчивости структуры климатического поля ветра над Мировым океаном. Рассмотрен внутригодовой ход положений центров основных циклонов и антициклонов. Обсуждена вероятность появления вторых центров в вихревых структурах и дополнительных вихревых образований на удалении от основного вихря. Проведен анализ регионального распределения тренда скорости приземного ветра. Дана оценка корреляционной связи её зональной и меридиональной компонент. На основі середньомісячних значень компонент вектору швидкості приземного вітру за період 1948–2012 рр. досліджено внутрішньорічну мінливість структури кліматичного поля вітру над Світовим океаном. Розглянуто внутрішньорічний хід положень центрів основних циклонів та антициклонів. Обговорено ймовірність появи других центрів у вихрових структурах і додаткових вихрових утворень на віддаленні від основного вихору. Проаналізовано регіональний розподіл тренду швидкості приземного вітру. Оцінено кореляційний зв’язок її зональної та меридіональної компонент. On the basis of the monthly average values of wind velocity components of the above-ground level an investigation of the intraannual variability of the wind climatic field structure above the World Ocean is carried out during 1948–2012. The intraannual motion of the centers location of the major cyclones and anticyclones is considered. The analysis of the wind field climatic maps shows that the centers location of the basic cyclones and anticyclones practically does not change. The probability of the second centers appearing into vortical structures and additional vortical formations occurring away from the main vortex is estimated. The analysis of the trend regional distribution of the above-ground level wind velocity is carried out. Areas of positive and negative trends are shown and estimations of their values are obtained. The correlation estimation of zonal and meridional wind velocity components of the above-ground level is given. In the regional distribution fields of a correlation coefficient and the hypothesis of no correlation, the areas of a positive and negative correlation coefficient and the areas with a high probability of no correlation between wind climatic velocity components are noted.